2020
DOI: 10.1016/j.lfs.2020.118317
|View full text |Cite
|
Sign up to set email alerts
|

GRP78 targeting: Hitting two birds with a stone

Abstract: Background Glucose regulating protein 78 (GRP78) is one member of the Heat Shock Protein family of chaperone proteins (HSPA5) found in eukaryotes. It acts as the master of the Unfolded Protein Response (UPR) process in the lumen of the Endoplasmic Reticulum (ER). Scope Under the stress of unfolded proteins, GRP78 binds to the unfolded proteins to prevent misfolding, while under the load of the unfolded protein, it drives the cell to autophagy or apoptosis. Several attem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
70
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 93 publications
(78 citation statements)
references
References 121 publications
1
70
0
1
Order By: Relevance
“…In this letter, we propose to shed light on the effect of the new variant mutation N501Y of the RBD on the viral recognition by the host cell-surface GRP78. This recognition can be targeted by peptides, antibodies, and phytochemicals ( 10 ).…”
mentioning
confidence: 99%
“…In this letter, we propose to shed light on the effect of the new variant mutation N501Y of the RBD on the viral recognition by the host cell-surface GRP78. This recognition can be targeted by peptides, antibodies, and phytochemicals ( 10 ).…”
mentioning
confidence: 99%
“…The relative transcript levels of Eif2ak3 [encoding the protein PERK ( Hayes et al, 1999 )], Atf4 [encoding the protein ATF4 ( Karpinski et al, 1992 )], Ddit3 [encoding the protein CHOP ( Marola et al, 2019 )], Ppp1r15a [encoding the protein GADD34 ( Clavarino et al, 2012 )], Hspa5 [encoding the protein GRP78 ( Elfiky et al, 2020 )], Hsp90B1 [encoding the protein GRP94 ( Chen et al, 2005 )], and Tnfrsf10B [encoding death receptor 5 (DR5; Dittmann et al, 2020 )] were significantly increased in the GA muscle of the tumor-bearing vehicle-treated group compared to the tumor-free vehicle-treated group ( p < 0.0001 for all comparisons) ( Figure 4 ). Curiously, relative transcript levels of Ern1 [encoding inositol requiring enzyme 1α (IRE1α; Tirasophon et al, 1998 )] were significantly reduced in the tumor-bearing vehicle-treated group compared to the tumor-free vehicle-treated group ( p = 0.001) ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Many reports showed that different natural product derived compounds have promising results against inflammation and viral infections including the newly emerged viral infection (SARS-CoV-2) 15,38–40 . Different natural compounds and their derivatives proved its binding affinity against different SARS-CoV-2 and host-cell targets 38,39,41 .…”
Section: Resultsmentioning
confidence: 99%